Study of the thermal stability and decomposition behaviour of Lu(NH4)(C2O4)2·2H2O. (30th May 2022) - Bao, Xinjun; Fang, Xiekai; Luo, Fengxiang; Zhou, Rong; He, Bin; Zhou, Hengshu; Zhou, Debi
Abstract: Lu(NH4 )(C2 O4 )2 ·2H2 O has been successfully fabricated by the improved oxalate precipitation method. Its thermal stability and decomposition behaviour were investigated by using scanning electron microscopy, thermalgravimetric‐differantial scanning calorimetry and in situ high temperature X‐ray diffraction measurements. Despite substantial removal of oxide, carbon, nitrogen, and hydrogen elements, the scanning electron microscopy images clearly revealed that the precursor calcined Lu2 O3 products maintained well the morphology properties of the precursor. Moreover, TG‐DSC analysis demonstrated that the peak temperatures of the precursor to Lu2 O2 CO3 and Lu2 O2 CO3 to Lu2 O3 were 400°C and 630°C, respectively. Finally, and most importantly, the in situ XRD results exhibited that the 'Lu(NH4 )(C2 O4 )2 ', 'Lu2 O2 CO3 ' and 'Lu2 O3 ' crystal structures formed by heating the Lu (NH4 ) (C2 O4 )2 ·H2 O at 25∼220°C, 400∼680°C and 680∼980°C, respectively. The experimental results provided an interesting fact that Lu(NH4 )(C2 O4 )2 ·H2 O has been completely decomposed into cubic phase Lu2 O3 crystal at 680°C, which is nearly 200°C lower than that of lutetium oxalate tetrahydrate prepared by traditional oxalic acid precipitation process.